2013
DOI: 10.1038/cdd.2013.127
|View full text |Cite
|
Sign up to set email alerts
|

PTEN, here, there, everywhere

Abstract: Loss of function of the phosphatase and tensin homolog (PTEN) tumor suppressor is frequently found in many human malignancies. 1 PTEN antagonizes the phosphatidylinositide 3-kinase (PI3K) pathway 2 by dephosphorylating the 3 0 position of phosphatidylinositol (3,4,5)-trisphosphate [PtdIns(3,4,5)P 3 ] (or PIP3). 2,3 PIP3 serves as a second messenger whose levels in the plasma membrane are elevated following cell stimulation with growth factors, mediated by the activity of PI3Ks. Proteins containing pleckstrin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…As shown by many studies, PTEN and TP53 are frequently dysregulated in many human malignancies and play a crucial role in the regulation of proliferation and differentiation [ 42 44 ]. These studies have shown pro-tumoral effects of p53 inactivation in the stromal fibroblasts, as well as that genetic inactivation of PTEN in CAFs, potentiate both onset and progression of carcinomas [ 42 47 ]. It has been reported that BMP2 signaling activate Smad1, in turn inhibits TGF-β-induced PSC activation and ECM formation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown by many studies, PTEN and TP53 are frequently dysregulated in many human malignancies and play a crucial role in the regulation of proliferation and differentiation [ 42 44 ]. These studies have shown pro-tumoral effects of p53 inactivation in the stromal fibroblasts, as well as that genetic inactivation of PTEN in CAFs, potentiate both onset and progression of carcinomas [ 42 47 ]. It has been reported that BMP2 signaling activate Smad1, in turn inhibits TGF-β-induced PSC activation and ECM formation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is pivotal in the regulation of the receptor tyrosine kinase (RTK) PI-3 kinase (PI3K)/Akt signalling pathway and, as such, even small changes in PTEN expression have been shown to have major consequences for normal cellular function [ 2 5 ]. The PTEN protein translocates between the nucleus and the cytoplasm enabling PTEN-specific compartmentalised functions [ 6 , 7 ]. At the molecular level, PTEN expression and cellular abundance is tightly regulated at the transcriptional, post-translational and post-transcriptional levels.…”
Section: Introductionmentioning
confidence: 99%
“…TXN is a small protein that reduces oxidized proteins and supports peroxiredoxin (PRDX)-mediated H2O2 clearance (Figure 3) [21]. It also positively regulates the activity of PTP1B, the phosphatase of the tyrosine kinase PDGF-beta, leading to increased PDGF-beta signaling [20] and it negatively regulates the tumor suppressor PTEN [22, 23]. These functions point to an oncogenic role of TXN.…”
Section: Introductionmentioning
confidence: 99%